2019
DOI: 10.1029/2019ef001189
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent 2018 Hot Extremes Across Northern Hemisphere Due to Human‐Induced Climate Change

Abstract: Extremely high temperatures pose an immediate threat to humans and ecosystems. In recent years, many regions on land and in the ocean experienced heat waves with devastating impacts that would have been highly unlikely without human‐induced climate change. Impacts are particularly severe when heat waves occur in regions with high exposure of people or crops. The recent 2018 spring‐to‐summer season was characterized by several major heat and dry extremes. On daily average between May and July 2018 about 22% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
218
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(230 citation statements)
references
References 41 publications
(72 reference statements)
9
218
1
2
Order By: Relevance
“…Global Change Research Program, 2018). These case studies are consistent with the long-term projections for climate change impacts for extreme heat (Christidis et al, 2011;Hansen et al, 2006;Meehl et al, 2007;Vogel et al, 2019;Zwiers et al, 2011), hurricanes (Keellings & Hernández Ayala, 2019), harmful algal blooms (Hilborn et al, 2014;Poh et al, 2019) and other extreme weather (Nilsen et al, 2011;Papalexiou & Montanari, 2019); allergenic pollen (Anenberg et al, 2017;L. H. Ziska et al, 2019), ozone air pollution (Fann et al, 2015;Kinney, 2018), wildfires (Abatzoglou & Williams, 2016;Liu et al, 2016), West Nile virus (Belova et al, 2017;Paull et al, 2017), and Lyme disease (Monaghan et al, 2015).…”
Section: Case Study Selectionsupporting
confidence: 73%
“…Global Change Research Program, 2018). These case studies are consistent with the long-term projections for climate change impacts for extreme heat (Christidis et al, 2011;Hansen et al, 2006;Meehl et al, 2007;Vogel et al, 2019;Zwiers et al, 2011), hurricanes (Keellings & Hernández Ayala, 2019), harmful algal blooms (Hilborn et al, 2014;Poh et al, 2019) and other extreme weather (Nilsen et al, 2011;Papalexiou & Montanari, 2019); allergenic pollen (Anenberg et al, 2017;L. H. Ziska et al, 2019), ozone air pollution (Fann et al, 2015;Kinney, 2018), wildfires (Abatzoglou & Williams, 2016;Liu et al, 2016), West Nile virus (Belova et al, 2017;Paull et al, 2017), and Lyme disease (Monaghan et al, 2015).…”
Section: Case Study Selectionsupporting
confidence: 73%
“…Because the CMIP5 Historical and Natural simulations were only run through 2005 (48,49), simulations using the actual climate forcings do not cover the most recent period of observations. Attribution analyses that use CMIP5 can thus either restrict the historical analyses to this pre2006 period [e.g., (4-6, 12, 20)] or use the early period of the CMIP5 future pro jections to extend the historical simulations (in which case the an thropogenic and nonanthropogenic simulations cover different time periods) [e.g., (8,38)]. In the case of previously published global attri bution analyses, which used the CMIP5 Historical and Natural simulations to quantify the influence of historical forcing on the probability of unprecedented hot, wet, and dry extremes at each area of the globe, the attribution analysis was limited to the pre2006 period (5).…”
Section: Introductionmentioning
confidence: 99%
“…European heatwave had considerable impacts on water management, agriculture, and nature reserve protection (Vogel et al, 2019;Arcadis, 2019). Hence, the grand challenge for national and regional water managers is to optimize water availability for di erent functions according to users' demands.…”
Section: Soil Moisture Information For Water Managementmentioning
confidence: 99%
“…We give an example application of the SWDI drought indicator for the dry summer period of 2018, as Vogel et al (2019) showed that heat waves will occur more frequently in the future. Martinez-Fernandez et al (2015) de ne the SWDI as:…”
Section: Translating Data Into Informationmentioning
confidence: 99%
See 1 more Smart Citation